Analisis Pengendalian Kualitas Proses Produksi Percetakan dengan Pendekatan Metode Lean Six-Sigma untuk Efisiensi - Muhammad Andi Rivaldi; Wiku Larutama; Pebi Yuda Pratama (Pusat riset dan Inovasi Nasional, 2025)
This study aims to analyze and improve the quality control of packaging printing production at PT XYZ by applying the Lean Six Sigma methodology. Lean Six Sigma combines waste reduction principles with statistical quality control to achieve operational excellence. The research identifies major production challenges, including high defect rates, overproduction, and ineffective inventory management, all of which contribute to increased costs and reduced efficiency. The DMAIC framework—Define, Measure, Analyze, Improve, and Control—was employed to systematically address these issues. During the Define and Measure phases, types of waste were identified and defect rates were calculated using Defects Per Million Opportunities (DPMO). In the Analyze phase, root causes were examined using a Fishbone (Ishikawa) diagram, highlighting factors related to manpower, materials, machines, and methods. The analysis revealed a sigma level of 3.2, indicating a moderate level of process quality and substantial room for improvement. To address the identified issues, several improvement strategies were proposed. These include implementing a Just-In-Time (JIT) system to reduce inventory waste, adopting the First-In-First-Out (FIFO) inventory method for better material rotation, and conducting targeted technical training for operators to minimize human error. In the Control phase, the study suggests process standardization, routine inspections, and continuous monitoring as key practices to ensure that improvements are sustained over time. The findings and recommendations from this study are expected to contribute to better quality control, reduced operational waste, and enhanced productivity in the packaging printing process. Ultimately, this approach aims to strengthen PT XYZ’s competitiveness in the printing industry by fostering a culture of continuous improvement and quality excellence.